The Influence of Brand Image, Brand Satisfaction, and Brand Experience on Brand Loyalty Mediated by Brand Trust - Ayu, Nandani Dwi Sukmaning; Nasir, Moechammad (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
This research aims to examine the impact of Brand Image, Brand Satisfaction, Brand Experience on Brand Loyalty, with Brand Trust acting as a mediator, in the Gacoan Noodle Brand franchise in the Greater Solo area. The research employs a quantitative approach. The study's population consists of individuals who have visited the Gacoan Noodle franchise in the Greater Solo region. The sampling method employed is non-probability sampling using a purposive sampling technique. Primary data is utilized for data collection, with 250 respondents participating in the study. A questionnaire, based on a Likert scale, was designed using an interval scale format. The data analysis method used in this study is Partial Least Squares (PLS), performed with SMARTPLS 3.0 software. The PLS-SEM analysis consists of two models: the Inner model and the Outer model. The findings indicate that the Brand Trust variable plays a significant role in mediating the relationship between Brand Image, Brand Satisfaction, Brand Experience, and Brand Loyalty for the Gacoan Noodle brand in the Greater Solo area.